THE COMPETENCE OF THE EIGHT GRADE STUENTS OF SMP SANTO MICHAEL IN IDENTIFYING CATAPHORIC, ANAPHORIC, EXOPHORIC IN THE JAKARTA POST NEWSPAPERS - Sarira Pongsapan (UKI TORAJA, 2016)
The objective of this research is to find out the competence of the eight grade studentsof SMP Santo Mickael in identifying cataphoric, anaphoric, exophoric in Jakarta postarticle. The population of this research was the eight grader students, academic year2015/2016.In the data were analyzed, found that in this study the students had difficulty inidentifying cataphoric, anaphoric, exophoric in Jakarta post article they still mademany errors. The result of the research shows that the mean score of identifyingcataphoric, anaphoric, exophoric in Jakarta post article is 23,16. The fact shown thatthe eight grade students have problems in comprehending cataphoric, anaphoric,exophoric.Based on the result of the research, the researcher concludes that the students’competence in identifying cataphoric, anaphoric, exophoric still low. It means thatteacher should pay attention in ELT process.